Implementation of Community Governance in the Field of Education - Djunaidi, Djunaidi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this article is to describe the implementation of community governance in education. This article is expected to provide an overview and perspective on community governance and the successful implementation of education to achieve community governance in Indonesia. In this article, the method used is descriptive qualitative, using secondary data. The sources used to obtain data in this study are journals and books that support research studies, namely about community governance in the field of education. The results obtained in this study are the implementation of governance observed from transparency, participation, and accountability in schools. Educational governance covers various aspects such as the application of curriculum and learning, facilities and infrastructure as well as education financing. There are also problems in implementing this community governance, namely in implementing school governance not all teachers have IT skills, there are limited teachers in developing teaching materials (KI/KD) and learning methods, limited school facilities and infrastructure, limitations of parents in learning assistance and the economic limitations of parents in supporting distance learning.